Non-linear aeroelastic response of high aspect-ratio wings in the frequency domain. (11th May 2017) - Afonso, F.; Vale, J.; Oliveira, É.; Lau, F.; Suleman, A.
ABSTRACT: A current trend in the aeronautic industry is to increase the wing aspect ratio to enhance aerodynamic efficiency by reducing the induced drag and thus reduce fuel consumption. Despite the associated benefits of a large aspect ratio, such as higher lift-to-drag ratios and range, commercial aircraft usually have a relatively low aspect ratio. This is partially explained by the fact that the wing becomes more flexible with increasing aspect ratio and thus more prone to large deflections, which can cause aeroelastic instability problems such as flutter. In this work, an aeroelastic study is conducted on a rectangular wing model of 20 m span and variable chord for a low subsonic speed condition to evaluate the differences between linear and non-linear static aeroelastic responses. Comparisons between linear and non-linear displacements, natural frequencies and flutter boundary are performed. An in-house non-linear aeroelastic framework was employed for this purpose. In this work, the influence of the aspect ratio and geometric non-linearity (highly deformed states) is assessed in terms of aeroelastic performance parameters: flutter speed and divergence speed. A nearly linear correlation of flutter speed difference (relative to linear analysis results) with vertical-tip displacement difference is observed. The flutter and divergence speeds vary substantially as the wing aspect ratio increases, and the divergence speeds always remain above the flutter speed. Furthermore, the flutter mechanism was observed to change as the wing chord is decreased.